Coastal and Marine Geo-Information Systems Applying the Technology to the Environment - Green, David R. 1956-; King, Stephen D. 1963- (Coastal Systems and Continental Margins, 2003)
The emphasis now placed on the concept of sediment cells as boundaries for coastal defence groups, and the development of SMPs, should help CPAs realise the importance of natural processes at the coast when designing defence and protection schemes. However, this will only be the case where defence groups exist, and where CPAs take up the challenge of developing SMPs. Coastal landscapes have been produced by the natural forces of wind, waves and tides, and many are nationally or internationally important for their habitats and natural features. Past practices at the coast, such as the construction of harbours, jetties and traditional defence systems may have contributed to the deterioration of the coast. English Nature (1992) have argued that if practices and methods of coastal defence are allowed to continue, then coastlines would be faced with worsening consequences, including: The loss of mudflats and the birds which live on them Damage to geological Sites of Special Scientific Interest (SSSIs) and scenic heritage by erosion, due to the stabilisation of the coast elsewhere Cutting of sediment supplies to beaches resulting in the loss of coastal wildlife Cessation through isolation from coastal processes, of the natural operation of spits, with serious deterioration of rare plants, animals and geomorphological and scenic qualities (English Nature, 1992) A number of designations, provided by national and international legislation do exist to aid conservation